Friction stir welding of polycarbonate lap joints: Relationship between processing parameters and mechanical properties. (October 2019) - Aghajani Derazkola, Hamed; Simchi, Abdolreza; Lambiase, Francesco
Abstract: The relation between process parameters and properties of polycarbonate (PC) sheet after friction stir welding (FSW) was investigated. Effects of FSW tool rotation speed ( ω ), travelling speed ( V ), tilt angle ( α ) and plunge depth on material flow, joint tensile strength, flexural strength, impact energy and hardness were investigated. It is shown that at low and high levels of heat input sound joints cannot be attained. At low heat inputs, the local temperature is not high enough to decrease the viscosity of the polymer to fill the interface, and thus voids and large planar cracks are formed in the joint root and stir zone. At high heat inputs, expelling of materials due to high peak temperature occurs. The stir zone is opaque due to changes in carbon chains as well as polymer degradation. Circular rings are appeared at the upper surface of the seam. The size of heat affected zone and stir zone is shown to significantly vary with the processing parameters. A change in the morphology of stir zone with the tilt angle is also shown. A sound joint with the highest strength is attained at ω = 2200 rpm, V = 105 mm/min, α = 2.5° and 1.2 mm tool plunge depth. The highest tensile strength, flexural strength and impact energy were respectively, 82% ( 55 MPa), 76% ( 61 MPa) and 75% ( 19 kJ/m 2 ). Fractographic studies show the presence of divergent lines of the surface, which develop outward from the crack initiation region. Highlights: Polycarbonate lap joints produced with friction stir welding (FSW) technique. Influence of friction stir welding process parameters (like tool rotational velocity, tool travelling speed, tool tilt angle and tool plunge depth) on heat generation and material flow of polycarbonate joint was assessed. The effects of process parameters on mechanical behaviors of polycarbonate joint was assessed.